Investment Company Uses Multiple Attributes in Decision Making: A Fuzzy Approach: An integrated approach to decision making in investment companies (Journal of Advances and Scholarly Researches in Allied Education, 2022)
One definition of decision making is the act of selecting one or more alternatives from a set thatare deemed desirable enough to be pursued in order to reach a goal or set of objectives. The decisionmakingprocess is quite unpredictable. Therefore, it is essential for a useful decision aid to be able tohandle imprecise and confusing information, such as huge profits, rapid speed, and cheap price.Diversity of thought, perspective, and belief must be honored. A decision model that takes intoconsideration the identification, evaluation, and combination of criteria and alternatives is needed torepresent the decision-making and evaluative processes in a fuzzy situation. Sometimes, we're facedwith a dilemma that requires us to choose the optimal course of action based on a single factor, such thepotential financial reward or the level of personal danger involved. However, the key to solving mostproblems in the real world is learning to make judgments based on a wide range of information.